The Problem of Murabaha Financing of Islamic Microfinance Institution and The Handling Strategies in Indonesia: A Literature Review - Azhar Alam; Ririn Tri Ratnasari; Nida’ Al-Karimah Makkawi; Aminudin Ma’ruf (AL-MUZARA'AH, 2023)
Indonesia is a country with the largest Muslim population in the world and has extraordinary potential in the amount and assets of Islamic microfinance and can be a reference for the application of Islamic Microfinance in other countries. The purpose of this study was to review the problems in murabaha financing at Islamic Microfinance Institution (IMFI) and the treatments. The approach used was a qualitative analysis of Indonesian literature studies about the specific type of murabaha financing with content analysis and thematic analysis techniques. This study found that internal and external factors caused problematic murabaha financing in BMT. Internal factors include the inaccuracy of BMT in 5C (Character, Capacity, Capital, Collateral, and Condition), lack of supervision, procedures violations, facilities and infrastructure, and lack of human resources (HR). Meanwhile, external factors include bad customers, unexpected circumstances of customers, lack of customer income, inflation, and government policies. The actions done by the BMTs to overcome problematic murabaha financing were by implementing BMT guidelines for prospective customers, preventing and repressive supervising, applying a democratic leadership style, applying fines, rescheduling, restructuring and reconditioning write off, auction of collateral, and legal actions. This study recommends strengthening financing selection by improving human resource skills and also variations in handling murabaha financing with a humanist approach.